Analisis Kesantunan Berbahasa Dalam Program Acara Overa Van Java Episode Pengambil Setan - Aisah, Cucu; Chandra, Putri Ayu; Nurjannah, Yuli Yuliyanti; Latifah, Latifah (IKIP Siliwangi, 2018)
Speaking is an activity when a person uses language to convey a particular purpose and purpose to others. Therefore, if discussing about the language can not be separated from the problem of language assistance itsel. This study intends to analyze language politeness in the Opera Van Java episode Pengambil Setan. This analysis is based on the theory of language assisted by Geoffrey Leech.Based on the results of this analysis concluded that violations of the maxim of awards in the event more, this triggers the foolness between the players and spectators in the program.